NEW DIRECT ORAL ANTICOAGULANTS FOR TREATMENT OF PATIENTS WITH ATRIAL FIBRILLATION IN REAL-WORLD SETTING - Zh. D. Kobalava; S. V. Villevalde; A. A. Shavarov (Столичная издательская компания, 2018)
Large randomized clinical trials (RCTs) in patients with non-valvular atrial fibrillation (AF) showed that new direct oral anticoagulants (DOACs) were just as effective at preventing stroke and systemic thromboembolic (STE) complications as warfarin, although DOACs were associated with less risk of intracranial bleeding. There was significant increasing number of publications addressed to use of DOACs in real-world setting in recent years. We discussed some of pros and cons for studies used real-world data in the review. Results of real-world studies provided a generally strong support for conclusions of main RCTs. In comparison of different DOACs against each other apixaban demonstrated lower bleeding risk while patients given rivaroxaban appeared to have higher rate of hemorrhagic events. High adherence to apixaban treatment for AF irrespective to additional value educational program suggested that apixaban treatment is easy to follow and well accepted by patients despite of twice-daily dosing regimen. Healthcare cost analyses demonstrated that patients who were prescribed apixaban had lower stroke/STE-related as well as major bleeding-related medical costs.